HRM Perspective on Transformational Leadership and Employee Performance: The Mediating Role of Digital Information Technology and Work Environment - Usep Suherman; Eri Novari; Husni Rofiq; Suteja Wira Dana Kusuma (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose: This study aims to examine and explain the effect of transformational leadership on employee performance, with digital information technology and work environment serving as mediating variables in West Java's Islamic banking sector. Design/methodology/approach: This study employed a quantitative survey design using non-probability purposive sampling. Data were collected from 280 supervisors and employees of Islamic banking institutions in West Java, Indonesia. The proposed hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. Findings: The results demonstrate that transformational leadership has a significant and positive effect on digital information technology adoption, work environment, and employee performance. Specifically, the work environment significantly mediates the relationship between transformational leadership and employee performance, as indicated by the indirect effect coefficient (β = 0.559, p < 0.000). In contrast, the mediating effect of digital information technology was found to be statistically insignificant. This is further supported by a p-value of 0.113, which is greater than the 0.05 significance level. Although transformational leadership encourages the use of digital information technology, technological factors alone do not significantly translate into improved employee performance without a supportive work environment. Research Implications: Islamic banking institutions should strengthen transformational leadership and prioritize a supportive work environment that fosters collaboration and employee well-being. Additionally, investments in digital technology must be accompanied by organizational improvements to maximize their impact on employee performance. Originality/Value: This study contributes to leadership and HRM literature by proving that in Islamic banking, the work environment is a much stronger mediator than digital information technology in explaining how transformational leadership enhances employee performance.